Difficulties and distress experienced by Japanese public health nurses specializing in quarantine services when dealing with COVID-19: A qualitative study in peri-urban municipality - Akari Miyazaki; Naoko Kumada Deguchi; Tomoko Omiya (AIMS Press, 2023)
Public health nurses (PHNs) are among the few municipal civil servants who lead community infection control and prevention initiatives in Japanese public health centers (PHCs). This study aims to investigate the distress faced by PHNs and clarify their difficulties and working environment relative to infection prevention control activities during the COVID-19 pandemic. We adopted a qualitative description methodology in this study of 12 PHNs who were involved in COVID-19 prevention and control in PHCs in Prefecture A. The distress during the early phase of the pandemic was due to the uncertainty of the SARS-CoV-2 related disease, which caused panic in medical institutions and among residents. PHNs were overwhelmed, distressed and exhausted by their inability to control the 'pandemic', lack of patient cooperation for prevention control and the unsustainable organizational environment. They were also distressed because they were one of the specialized personnel responsible for saving residents' lives with limited medical resources and while having identity crises due to an inability to carry out the PHN's role of controlling infection in the community. For future crises, rapid, drastic innovation defying conventional organizational systems is critical to reform sustainable organizations so that they play an effective role in the community. Innovation in crisis communication and strengthening the medical system will help achieve a resilient community in a health crisis.